Prebiotic and probiotic agents enhance antibody-based immune responses to Salmonella Typhimurium infection in pigs - Naqid, Ibrahim A.; Owen, Jonathan P.; Maddison, Ben C.; Gardner, David S.; Foster, Neil; Tchorzewska, Monika; La Ragione, Roberto M.; Gough, Kevin C. (Elsevier, 2015)
Salmonellosis causes significant economic losses to the pig industry and contaminated pork products are an important source of Salmonella for humans. The EU ban on the use of antibiotic growth promoters in pig production, and the emergence of antibiotic resistance has meant there is a pressing need for alternative control strategies for pathogenic bacteria such as S. Typhimurium in pigs. Here, we determined the effects of prebiotic, probiotic and synbiotic diet regimes on antibody responses to oral Salmonella challenge of pigs. The data demonstrate that the inclusion of the probiotic Lactobacillus plantarum B2984 in the diet of piglets (∼1 × 1010 cfu/animal/day) enhanced serum IgM (P<0.001), IgG (P=0.001) and IgA (P=0.039) responses to S. Typhimurium infection including cross-reacting antibodies to S. Enteritidis. Similarly, inclusion of the prebiotic lactulose at 1% (w/w) of the feed on a daily basis in the diet enhanced serum IgM (P=0.010), IgG (P=0.004) and IgA (P=0.046) responses to S. Typhimurium infection and also cross-reacting antibodies to S. Enteritidis. Inclusion of both additives in the synbiotic diet also elicited an enhanced immune response with IgM (P=0.009) and IgG (P=0.046) levels being increased, however a significant interaction of the pre and probiotics was observed when considering the immune responses to S. Typhimurium (IgM P=0.004; IgG and IgA, P<0.001 for interaction). With respect to immune responses, the effects of pre or probiotic administration were the same or reduced in the synbiotic diet compared to when used in isolation. The data support the use of Lactobacillus plantarum B2984 or lactulose as strategies to contribute to the protection of weaned piglets from zoonotic bacterial pathogens, but caution must be taken when combining dietary supplements as combinations can interact.